CELLS INVOLVED IN THE IMMUNE RESPONSE : XII. THE DIFFERING RESPONSES OF NORMAL RABBIT LYMPHOID CELLS TO PHYTOHEMAGGLUTININ, GOAT ANTI-RABBIT IMMUNOGLOBULIN ANTISERUM AND ALLOGENEIC AND XENOGENEIC LYMPHOCYTES - Daguillard, Fritz (The Rockefeller University Press, 1969)
Cells of the different lymphoid organs in the normal adult rabbit were investigated for their capacity to respond in vitro to a number of stimuli, such as phytohemagglutinin (PHA), anti-rabbit immunoglobulin antiserum (GARIG) and allogeneic and xenogeneic lymphoid cells, and for their capacity to adsorb radioactively-labeled anti-immunoglobulin antiserum. The bone marrow cells responded minimally to PHA, GARIG, and the allogeneic and xenogeneic stimuli. The thymus cells were unable to respond to stimulation with GARIG although they responded to the other stimuli. The cells of the other lymphoid organs tested responded to all the mitogenic agents, to varying degrees. On the basis of the results presented and the findings of other investigators, it is concluded that: 1. The response of the cells to GARIG indicates a potential capacity to mediate humoral immunity and requires the presence of immunoglobulin or immunoglobulin-like recognition sites on the cell surface. 2. The response of the cells to PHA and allogeneic and xenogeneic cells indicates a potential capacity to mediate cellular immunity and does not necessitate the presence of immunoglobulin-recognition sites on the cell surface. 3. The thymus in the normal adult rabbit consists of cells capable of mediating cellular immunity only. 4. The other lymphoid organs appear to possess cells capable of mediating humoral and cellular immunity.